(untitled) (International Journal of Engineering and Computer Science, 2015)
Research institutions adopting Enterprise Resource Planning packages for their day to day operations generate enormous data. Effective methodology for analysis these data will add value to the research and provide in the decision making process for the management using Business Intelligence (BI) models. For accomplishing this task, specific rules, techniques and algorithms needs to be developed in order to make the ERP system intelligent. These rules will bring out the hidden Business Intelligence in the ERP data and thereby will improve the outcome and deliverables of the project apart from providing support to the scientist. This forms a cyclic structure by again analyzing the outcome of the intelligence found, as this intelligence is incorporated with the ERP database itself. BI has been found used extensively in manufacturing sector and business houses and seldom used in R&D institutions and laboratories. This research work envisages to use BI model to improve the performance and provide support to large R&D labs like Council of Scientific and Industrial Research (CSIR).